2017
DOI: 10.1002/eco.1911
|View full text |Cite
|
Sign up to set email alerts
|

Water regime of reclaimed and unreclaimed post‐mining sites

Abstract: Water regime, throughfall, stemflow, soil water storage, subsurface runoff, and meteorological parameters were studied during 2 years (2011–2012) in 2 reclaimed and 2 unreclaimed post‐mining sites near Sokolov (Czech Republic). All sites were 25–35 years old, covered by woody vegetation, and developed on the same overburden consisting of tertiary clays. Interception of water by vegetation was about one third of precipitation in both reclaimed and unreclaimed sites; stemflow also did not differ significantly be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
1
7
2
Order By: Relevance
“…This means that alder sites have higher water field capacity but also higher wilting point as compared to regrowth sites (Figure 2). The water regime at both sites after 30 years of development was basically similar, but higher moisture and consequently higher soil-water storage were found at the alder plantation (Figure 3), which is consistent with the already reported high water field capacity at these sites [12,30,39].…”
Section: Upscaling Small-scale Processes To Whole Soil Profile Develosupporting
confidence: 89%
See 3 more Smart Citations
“…This means that alder sites have higher water field capacity but also higher wilting point as compared to regrowth sites (Figure 2). The water regime at both sites after 30 years of development was basically similar, but higher moisture and consequently higher soil-water storage were found at the alder plantation (Figure 3), which is consistent with the already reported high water field capacity at these sites [12,30,39].…”
Section: Upscaling Small-scale Processes To Whole Soil Profile Develosupporting
confidence: 89%
“…It seems that soil-water storage is closely linked with SOM storage. Similarly, as proposed by Cejpek et al [39], plants with a fast-growing strategy, which tend to store more SOM in mineral soil [3,6], also tend to produce soil aggregates with more bound OM [20] and, consequently, soils store more water [19,22,30,39]. This concept opens many other questions, such as how these parameters relate to the water balance (e.g., to runoff and evapotranspiration), how historical changes in soil carbon storage and water retention affect subsequent ecosystem development, and many others.…”
Section: Potential Of Using Controlled Catchments In the Study Of Watmentioning
confidence: 66%
See 2 more Smart Citations
“…They found that by improving soil hydraulic conditions, composts and sewage sludge greatly improved plant growth, whereas gravel and woodchip mulches applied to the soil surface had little impact on plant responses or soil properties. A longer‐term study on vegetation succession impacts on the soil water regime of post‐mining soils that had either been reclaimed or left to natural recovery is presented by Cejpek et al (). They found that in the 30 years since mining ceased, the water regime on the mining sites was similar to surrounding forests and that spontaneous forest regrowth in unreclaimed areas resulted in a similar water regime to reclaimed areas.…”
mentioning
confidence: 99%